Pathogen-triggered changes in plant development: Virulence strategies or host defense mechanism? - Kong, Feng; Yang, Li (Frontiers in Microbiology, 2023)
Plants, as sessile organisms, are constantly exposed to pathogens in nature. Plants rely on physical barriers, constitutive chemical defenses, and sophisticated inducible immunity to fight against pathogens. The output of these defense strategies is highly associated with host development and morphology. Successful pathogens utilize various virulence strategies to colonize, retrieve nutrients and cause disease. In addition to the overall defense-growth balance, the host-pathogen interactions often lead to changes in the development of specific tissues/organs. In this review, we focus on recent advances in understanding the molecular mechanisms of pathogen-induced changes in plants' development. We discuss that changes in host development could be a target of pathogen virulence strategies or an active defense strategy of plants. Current and ongoing research about how pathogens shape plant development to increase their virulence and causes diseases could give us novel views on plant disease control.